Antinociceptive and antiedematogenic activities of andrographolide isolated from Andrographis paniculata in animal models. - Sulaiman, Mohd Roslan; Zakaria, Zainul Amiruddin; Rahman, Ab Abdul; Tengku Mohamad, Tengku Azam Shah; Mohd Desa, Mohd Nasir; Stanslas, Johnson; Moin, Saidi; Israf Ali, Daud Ahmad (SAGE Publications, 2010)
The current study was performed to evaluate the antinociceptive and antiedematogenic properties of andrographolide isolated from the leaves of Andrographis paniculata using two animal models. Antinociceptive activity was evaluated using the acetic acid- induced writhing and the hot-plate tests, while antiedematogenic activity was measured using the carrageenan-induced paw edema test. Subcutaneous (s.c.) administration of andrographolide (10, 25, and 50 mg/kg) did not affect the motor coordination of the experimental animals but produced significant (p <.05) antinociceptive activity when assessed using both tests. However, 2 mg/kg naloxone failed to affect the 25 mg/kg andrographolide activity in both tests, indicating that the activity was modulated via nonopioid mechanisms. Furthermore, andrographolide showed significant (p <.05) antiedematogenic activity. In conclusion, the results obtained suggest that andrographolide has antinociceptive and antiedematogenic activities; it may be useful for treating pain and inflammation once human studies are conducted.